Subpleural multilevel intercostal continuous analgesia after thoracoscopic pulmonary resection: a pilot study - Bousema, Jelle E. (J Cardiothorac Surg, 2019)
BACKGROUND: Sufficient pain control and rapid mobilisation after VATS are important to enhance recovery and prevent complications. Thoracic epidural analgesia (TEA) is the gold standard, but failure rates of 9–30% have been described. In addition, TEA reduces patient mobilisation and bladder function. Subpleural continuous analgesia (SCA) is a regional analgesic technique that is placed under direct thoracoscopic vision and is not associated with the mentioned disadvantages of TEA. The objective of this study was to assess surgical feasibility, pain control and patient satisfaction of SCA. METHODS: Observational pilot study in patients who underwent VATS pulmonary resection and received SCA (n = 23). Pain scores (numeric rating scale 0–10) and patient satisfaction (5-point Likert scale) were collected on postoperative day (POD) 0–3. Secondary outcomes were the period of urinary catheter use and period to full mobilisation. RESULTS: Placement of the subpleural catheter took an average of 11 min (SD 5) and was successful in all patients. Pain scores on POD 0–3 were 1.2 (SD 1.2), 2.0 (SD 1.9), 1.7 (SD 1.5) and 1.2 (SD 1.1) respectively. On POD 0–3 at least 79% of patients were satisfied or very satisfied on pain relief and mobilisation. The duration of subpleural continuous analgesia was 4 days (IQR 3–5, range 2–11). Urinary catheters were used zero days (IQR 0–1, range 0–6) and full mobilisation was achieved on POD 2 (IQR 1–2, range 1–6). CONCLUSION: Subpleural continuous analgesia in VATS pulmonary resection is feasible and provides adequate pain control and good patient satisfaction. TRIAL REGISTRATION: This pilot study was not registered in a trial register.